Impact of Information Technology on Library Space Requirements (International Journal of Engineering and Computer Science, 2013)
This brief research paper was undertaken to determine whether the digitization of information (and other new technological processes) will provide any future space savings for the undergraduate academic library. While the author found evidence that the rate of growth for shelving space in some areas such as reference and periodicals may decline, he found just as much evidence that technology itself is increasing space requirements for the modern library. A concluding table summarizes the probable impact of technology on future space needs for the various major library functions; it shows no clear evidence that technology will help ameliorate such increased needs.